2021
DOI: 10.1128/jvi.02001-20
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase SHP2 Suppresses Host Innate Immunity against Influenza A Virus by Regulating EGFR-Mediated Signaling

Abstract: Influenza A virus (IAV) emerges as a highly contagious pathogen, causing acute respiratory illnesses in human beings and animals and frequently giving rise to epidemic outbreaks. Evasion of IAV from host immunity facilitates viral replication and spread, which can be initiated through various mechanisms, including epidermal growth factor receptor (EGFR) activation. However, how EGFR mediates the suppression of antiviral systems remains unclear. Here, we examined host innate immune responses and their relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Nevertheless, in the monolayer of hBMECs, there was no significant difference both in transcription and translation levels of EGFR at 12, 36, and 72 h post-infection (hpi) ( Supplementary Figure S1C ). Many viruses activate EGFR through phosphorylation at the early stage of infection, including ZIKV, PEDV, and IAV (Yang et al, 2018 ; Sabino et al, 2021 ; Wang et al, 2021 ). To figure out whether EGFR could be activated by JEV through phosphorylation, phosphorylation on tyrosine sites of EGFR in hBMECs at the early phase of JEV infection was examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in the monolayer of hBMECs, there was no significant difference both in transcription and translation levels of EGFR at 12, 36, and 72 h post-infection (hpi) ( Supplementary Figure S1C ). Many viruses activate EGFR through phosphorylation at the early stage of infection, including ZIKV, PEDV, and IAV (Yang et al, 2018 ; Sabino et al, 2021 ; Wang et al, 2021 ). To figure out whether EGFR could be activated by JEV through phosphorylation, phosphorylation on tyrosine sites of EGFR in hBMECs at the early phase of JEV infection was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Since EGFR does not affect JEV attachment and entry in hBMECs, how does EGFR facilitate JEV infection in hBMECs? It has been widely reported that EGFR participates in the regulation of host innate immunity during viral infection (Lupberger et al, 2013 ; Qiu et al, 2020 ; Wang et al, 2021 ). For example, respiratory virus (RSV) induced EGFR phosphorylation, which inhibited interferon regulatory factor 1 (IRF1)-regulate interferon-lambda (IFN-λ) production and breakdown of airway epithelium antiviral response (Kalinowski et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D4/21 cells were maintained in Roswell Park Memorial Institute 1640 Medium (Gibco, Thermo Fisher Scientific, Inc., Waltham, MA, USA), containing 10% FBS, 1% nonessential amino acids (Invitrogen, Carlsbad, CA, USA), 100 U/mL penicillin, and 100 μg/mL streptomycin. All cells were cultured at 37 °C under 5% CO 2 atmosphere, as previously described [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…GAPDH was used as a reference housekeeping gene for internal standardization. For quantification, the 2-ΔΔCt methods were used to calculate the relative RNA levels against the GAPDH [ 34 ].…”
Section: Methodsmentioning
confidence: 99%